Kebijakan Pendidikan Anak Berkebutuhan Khusus di Surabaya dalam Perspektif Islam - Rio Febriannur Rachman (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
This article discusses basic education programs for children with special needs in Surabaya. The program is carried out by the Surabaya City Education Office through the provision of Disability Service Centers or PDC, which are located in the West, East, North, South and downtown of Surabaya. In 2009, children with special needs were given learning facilities together with children without special needs through inclusive schools. In the inclusive school, there are Special Advisory Teachers (SPT) who have a bachelor's background in special education and a bachelor of psychology. In 2016, the inclusive school program that was already running was strengthened by the existence of PDC. This program is proof that Surabaya is serious about providing protection and services for people from various backgrounds or levels of society. This is also an effort to implement the spirit of the 1945 Constitution which is based on social justice principles, including in the field of education. The theory used in this article relates to basic education, counseling (because children with special needs need this intervention), and public policy. The method used is qualitative with a literature review approach. This article discusses how PDC's public policy is related to the concept of sustainable development outlined by the United Nations and the concept of the benefit of the Ummah that is emphasized by Islamic teachings. The results of this study show that the PDC program is compatible with sustainable social development and the spirit of fostering the benefit of the people. Thus, this program deserves to be continued, of course with the openness to make improvements at a later date, and is suitable for replication in other areas.